1985
DOI: 10.3758/bf03207137
|View full text |Cite
|
Sign up to set email alerts
|

Interaction space of Müller-Lyer with filled-unfilled illusion: An explanation of Müller-Lyer asymmetry

Abstract: The filled-unfilled space illusion was investigated as a possible explanation for the asymmetry (difference in strength) between tails-out and tails-in versions of the Miiller-Lyer illusion. Previous work has shown that removal ofthe horizontal shaft makes both configurations look shorter, but affects them unequally and only partially reduces the asymmetry. In two experiments, illusion strength was varied by use of either different tail lengths or single-vs. double-ended figures. Subjects used method of adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…The overall magnitude of the metric distortion was reduced with these configurations, but they still observed contraction for concave versions and expansion for convex versions. Similar results were reported by Beagley (1985) and Greist-Bousquet and Schiffman (1981 b). In the work that follows, we have studied whether the distortion differs when the shaft is present or absent and describe this as a manipulation of"shaft state.…”
Section: Key Variables For Metric Distortionsupporting
confidence: 81%
“…The overall magnitude of the metric distortion was reduced with these configurations, but they still observed contraction for concave versions and expansion for convex versions. Similar results were reported by Beagley (1985) and Greist-Bousquet and Schiffman (1981 b). In the work that follows, we have studied whether the distortion differs when the shaft is present or absent and describe this as a manipulation of"shaft state.…”
Section: Key Variables For Metric Distortionsupporting
confidence: 81%
“…It has been reported that asymmetries in the data may be partly due to a methodological artifact of the standard or control line (Beagley, 1985;Christie, 1975; see also Adam & Bateman, 1980), to the different spatial locations of the contextual stimuli in the two ML forms (Pressey & Smith, 1986), or to differences in attention between the two ML forms (Pressey & Pressey, 1992). Indeed it has been suggested that a single mechanism underlies the apex-in and apex-out ML illusion (Brigell & Uhlarik, 1979;Jordan & Uhlarik, 1986;Worrall & Firth, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…The former is referred to as filled space, and the latter as unfilled space. This phenomenon is referred to as an illusion of filled-unfilled space or an illusion of interrupted distance (Beagley, 1985;Lewis, 1912). If a line works as the unfilled space, the perceptual system of the phantom array or line could be identical to the function underlying the illusion of filled-unfilled space.…”
Section: Discussionmentioning
confidence: 99%